2023
DOI: 10.1111/1755-6724.15078
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Systems Characterized by Crustal Thermally‐dominated Structures of Southeastern China

Abstract: Southeastern China (SE China) is located in the Pacific tectonic domain and has experienced a series of tectono–magmatic activities induced by the subduction of the Paleo–Pacific Plate since the late Mesozoic. The subduction formed a series of NE‐NNE oriented faults under the NW‐SE regional stress field, along which a number of thermal springs occur. Previous studies have focused on the genesis mechanism of specific geothermal field in SE China, but the generality characteristic of hydrothermal systems in SE C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that the ore-forming fluid of the Dahongshan deposit was formed by mixing hightemperature with high-salinity and low-salinity fluids from mantle magma (Zhong et al, 1999;Wu et al, 2008). In addition, the protolith of the metavolcanic rocks exposed in the Dahongshan deposit is tholeiite and has the geochemical characteristics of the mid-ocean ridge environment, which is conducive for submarine hydrothermal circulation and metasomatism (Xu, 1998;Zhong et al, 1999;Ye et al, 2021;Gui et al, 2023). In contrast, the mixing of magmatic water with meteoric water reasonably explains the observed δ 18 O H2O values of gangue and ore minerals.…”
Section: Source Of Ore-forming Fluidsmentioning
confidence: 99%
“…Studies have shown that the ore-forming fluid of the Dahongshan deposit was formed by mixing hightemperature with high-salinity and low-salinity fluids from mantle magma (Zhong et al, 1999;Wu et al, 2008). In addition, the protolith of the metavolcanic rocks exposed in the Dahongshan deposit is tholeiite and has the geochemical characteristics of the mid-ocean ridge environment, which is conducive for submarine hydrothermal circulation and metasomatism (Xu, 1998;Zhong et al, 1999;Ye et al, 2021;Gui et al, 2023). In contrast, the mixing of magmatic water with meteoric water reasonably explains the observed δ 18 O H2O values of gangue and ore minerals.…”
Section: Source Of Ore-forming Fluidsmentioning
confidence: 99%
“…Geothermal researchers have carried out a series of studies on the thermophysical properties of rocks in the study area, including temperature field distribution, terrestrial heat flow, lithosphere thermal structure, and have gained a preliminary understanding of the basic characteristics of the present-day geothermal field (Jiang et al, 2016;Cui et al, 2019;Wang et al, 2019Wang et al, , 2023. Several studies have been completed on the characteristics…”
Section: Introductionmentioning
confidence: 99%